Recent strategies and trends in implanting of renewable energy sources for sustainability – A review. (2021) - Vivek, C.M.; Ramkumar, P.; Srividhya, P.K.; Sivasubramanian, M.
Abstract: Advancements in technology, industrial revolution and growth of world's population push for energy demand. In order to overcome energy demand, reducing the import cost and environmental protection developed countries and developing countries are concentrating towards the non-conventional and renewable sources of energy. For replacing the fossil fuels with renewable sources most of the countries has been move on to the cost effective techniques, technological requirements, geographical constraints etc. Most of the countries are in process of promoting the renewable sources for overcoming the hurdles. This paper focus on the assessment of renewable energy sources in various countries by highlighting their performance towards the implementation of the new strategies and their performance towards energy sustainability.